High-Efficiency Drug Characterization through Microchannel-Integrated Microfluidic Systems - Ravi, Bolleddu; Srinivas, Thangallapalli; Kumar, Kuntla Raj; Sudheera, Mannepalli (International Journal of Pharmaceutical Investigation, 2025)
Aim/Background Micro-channels, characterized by their minuscule size ranging from 10 µm to 200 µm, find diverse applications across various fields such as biomedical, electronics, and chemical reactors, etc. Here, it was showed that easy, simples and low-cost methods for the fabrication of complex structured micro-fluidic channels. Materials and Methods In addition, a new application was showed by using them. Importantly, in fabrication, initially, Acrylonitrile Butadiene Styrene (ABS) filaments were used to mould desired shape, later they are place in mould carefully. After this, Polydimethylsiloxane (PDMS) was poured into the mould followed by annealing which help to solidify the liquid PDMS. The remained ABS was removed by Acetone solvent. In this way, the various shapes of micro-fluidic channels were (80 µm) prepared. In a specific application scenario, these micro-fluidic channels were employed for characterization of drug, where substances like Tridax procumbens leaves extract was subjected to comprehensive testing for anti-fungal, anti-bacterial, and anti-viral properties. Results The fabrication technique is successfully produced complex microchannel structures with high precision. The microfluidic platform enabled effective drug characterization, showcasing its potential for rapid and efficient biological testing. Qualitative analysis revealed that the microchannel design positively influenced both analysis efficiency and response time. Conclusion This innovative approach not only facilitates the creation of intricate micro structures but also enhances the speed and accuracy of analytical processes. The integration of ABS filaments and PDMS in micro channel fabrication showcases a promising avenue for advancing point-of-care diagnostics with potential implications across various industries and research domains.
Keywords: Micro-fluidic channel; Polydimethylsiloxane; Tridax procumbens; Drug analysis